Biomechanical investigations of alpine ski tactics based on the distribution of velocity of running of the whole course - Erdmann, W. S.; Aschenbrenner, P.; Giovanis, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Among the most important biomechanical factors Influencing sport result in alpine skiing are: skier body build, their fitness level, technique and tactics of running, the equipment used, and external conditions. For many years up to now, tactics of running are limited primarily to choosing the proper line of running between the gates. The purpose of this paper is to describe investigations on tactics of running that take into account distribution of velocity of running along the whole course.